Cuticular Hydrocarbons as Contact Sex Pheromone in the Parasitoid Wasp Urolepis rufipes - Würf, Josef; Pokorny, Tamara; Wittbrodt, Johannes; Millar, Jocelyn G.; Ruther, Joachim (Frontiers in Ecology and Evolution, 2020)
The cuticle of virtually any insect is covered by a thin layer of cuticular hydrocarbons (CHCs) typically consisting of a complex mixture of n-alkanes, methyl-branched alkanes, and unsaturated hydrocarbons. Apart from their putative primary function as a desiccation barrier, CHCs are used by insects for communication. In many species of parasitoid wasps, males use CHCs to recognize females, and thus the composition of CHC profiles is typically species- and sex-specific. Sometimes, the biological activity of CHCs is synergized by more polar lipids. In most species, however, the contribution of polar lipids and the role of individual CHCs or CHC classes is unclear. Here we report a CHC-based contact sex pheromone in the pteromalid wasp Urolepis rufipes. Males of U. rufipes were arrested on and showed courtship behavior (wing fanning) and copulation attempts towards cadavers of females, whereas male cadavers and solvent-washed cadavers of either sex elicited no responses. Whole body extracts from females and the non-polar CHC fraction thereof elicited arrestment, courtship, and copulation attempts by males, whereas the fractions containing polar lipids were behaviorally inactive. Analyses of male- and female-derived CHC profiles revealed that they consisted exclusively of n-alkanes and methyl-branched alkanes. Removal of n-alkanes from female-derived CHCs with molecular sieves rendered the remaining methyl-branched fraction inactive. Synthetic n-alkanes in female-specific ratios also did not elicit any responses by males. Two 7-methylalkanes (7-MeC31 and 7-MeC33) were the only two components with a higher relative abundance in females compared to males. However, supplementation of male-derived CHCs with synthetic racemic 7-MeC31 and 7-MeC33 to levels found in females was not sufficient to render male-derived CHCs attractive to males. Enantiopure synthetic 7-MeC31 and 7-MeC33 might have caused different effects but were not available. We conclude that female-derived CHCs function as a contact sex pheromone in U. rufipes. Our data suggest that methyl-branched and n-alkanes act synergistically and that the sex-specific relative composition of the whole profile, rather than the abundances of single components, underlies the elicitation of male courtship behavior.